GeoNode condivisione di dati e applicazioni territoriali - Dalmasso, Simone; Casagrande, Luca (GEOmedia, 2012)
Negli ultimi anni si è passati da un sistema in cui la priorità era reperire le informazioni ad un sistema in cui la priorità è gestire l'imponente mole di dati disponibili e soprattutto rendere questi dati utili, cioè condividerli pensando anche ad un'utenza non necessariamente tecnica. GeoNode sharing of spatial data and land applications GeoNode is an open source platform that facilitates the creation, sharing, and collab-orative use of geospatial data. The project aims to surpass existing spatial data infra-structure solutions by integrating robust social and cartographic tools.At its core, the GeoNode has a stack based on GeoServer, Django, and GeoExt that provides a platform for sophisticated web browser spatial visualization and analysis (excerpt from GeoNode website).